2019
DOI: 10.1016/j.sjbs.2019.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival ratios of Cadra cautella (Lepidoptera: Pyralidae) different life stages after treated with ultraviolet radiation in dates

Abstract: Date palm, is a tree of economic importance which is grown around the world, including Saudi Arabia. Its fruit is nutritious and possesses medicinal benefits. Almond moth, is a serious date fruits pest in the field as well as in the storage and causes severe economic losses. In the given research, ultraviolet radiation type B (UV-B, 315 nm) harmful effects were evaluated against all developmental stages of C. cautella. One and 3-d-old eggs, 12 and 18-d-old larvae, 1-d and 6-d-old pupae, and 1-d-old adults, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(39 reference statements)
1
6
1
Order By: Relevance
“…In the embryonic development of insect eggs, specialization of different embryonic organs does not occur; thus, exposure to non-penetrating radiations like UVrays, do not damage the surface tissue of the eggs and can be fatal only at the advanced stages of egg development (Hori et al 2014). However, our results contrast with the findings of Alwaneen et al (2019) who observed that the younger eggs of Cadra cautella (Walker) were more sensitive than older ones.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…In the embryonic development of insect eggs, specialization of different embryonic organs does not occur; thus, exposure to non-penetrating radiations like UVrays, do not damage the surface tissue of the eggs and can be fatal only at the advanced stages of egg development (Hori et al 2014). However, our results contrast with the findings of Alwaneen et al (2019) who observed that the younger eggs of Cadra cautella (Walker) were more sensitive than older ones.…”
Section: Resultscontrasting
confidence: 92%
“…The present study showed that E. kuehniella eggs were very sensitive to UV-C radiation and there was no hatchability after 16 min of exposure. The harmful effects of UV on fertile eggs of other insect species have been observed and confirmed the sensitivity of eggs to UV light (Alwaneen et al 2019); In contrast, the eggs of, C. maculatous, were not very sensitive to UV and some larvae completed their life cycle even 50 min exposure to UV-C radiation (Heidari et al 2016).…”
Section: Resultsmentioning
confidence: 65%
“…Hatching % of eggs T. castaneum significantly reduced as time of UV-B light increased in contrast with control group. The results of present study are supporting the resulting of (Sorungbe et al, 2016;Alwaneen et al, 2019) who noticed the eggs of C. cautella are remarkable sensitive on ultraviolet radiations. Faruki et al (2007), Bakr (2013) moreover made known in the minimization in the rate of hatching percentage of eggs, T. castaneum, C. cautella, T. confusum and Tyrophagus putrescentiae mites on UV-C and UV-B light.…”
Section: Resultssupporting
confidence: 92%
“…The eggs of T. castenium, T. confusium [41,44] the mite Tyrophagus putrescentiae [60] and Cadra cautella [40], were sensitive to UV light. In contrast, the eggs sensitivity and duration of different life stages of C. maculatus, were not significantly affected at different exposure times [61].…”
Section: Discussionmentioning
confidence: 99%
“…UVC-irradiation is generally less harmful to living organisms than the ionizing radiation as they penetrate only the surface layer of cells [38]. A number of investigators have considered the possibility of using UV-irradiation to control, or at least to suppress the development of various species of stored product insects such as Heliothis virescens F. and H. zea (Boddie) [37], Ephestia cautella ) Walker) [39,40], Tribolium castaneum Duval [41,42], Alphitobius diaperinus (Panzer) [43], T. confusum, T. costaneum, Cadra cautella (Walker) [44][45][46], Trogoderma granarium Everts [47], Sitophilus zeamais (Motschulsky) [48], Mythimna separate [49] and Rhyzopertha dominica (Fab.) [50].…”
Section: Introductionmentioning
confidence: 99%